Bufalin targets the SRC-3/c-Myc pathway in chemoresistant cells to regulate metastasis induced by chemoresistance in colorectal cancer - Jinbao Chen; Chenqi Wu; Kun Yu; Jinpei Liu; Jiahua Yang; Wei Li; Xiaoxia Tang; Yihai Shi; Ke Xu; Yi Chen; Xiaoyu Qin (Journal of Cancer Research and Clinical Oncology)
Abstract Background Metastasis and chemoresistance are often major challenges in advanced-stage colorectal cancer. Bufalin has a therapeutic effect on both metastasis and drug resistance, but how bufalin affects chemoresistance-mediated metastasis remains unclear. Methods The role of BU in the inhibition of EMT and angiogenesis induced by chemoresistant cells using wound healing assays, invasion assays, HUVEC tube formation and adhesion assays. Western blot and immunofluorescence were used to explore the potential molecular changes. BU can precisely regulate c-Myc expression by targeting SRC-3 in chemoresistant cells was confirmed by Western blot. In vivo experiments were conducted to validate that both BU and cinobufacini can ameliorate drug resistance-promoted EMT and angiogenic effects. Results Bufalin inhibited resistance-induced epithelial-mesenchymal transition (EMT) and angiogenesis. Targeting of the SRC-3 protein by bufalin reduced the expression level of c-Myc and inhibited the prometastatic effect mediated by chemoresistance, and overexpression of SRC-3 or c-Myc reversed the inhibitory effect of bufalin on chemotherapeutic resistance, promoting metastasis. Moreover, the clinical drug cinobufacini and its main active monomer bufalin reduced liver metastasis of colorectal cancer caused by chemoresistance in vivo. Conclusion Bufalin can target the SRC-3/c-Myc signaling pathway to affect the prometastatic effect of chemoresistant cells, suggesting that bufalin may be used as a new adjuvant antimetastatic therapy for colorectal cancer.